The association of human immunodeficiency virus and skeletal metastases in breast cancer using Tc-99m methyl diphosphonate bone scan - Masha Maharaj; Nisaar Korowlay (World Journal of Nuclear Medicine)
Skeletal involvement occurs in 30%–70% of all cancer patients, with breast cancer (BC) being the leading cause for bone metastases in women and prostate cancer in men followed by lung cancer. Human immunodeficiency virus (HIV) is a lentivirus (a member of the retrovirus family) that causes acquired immunodeficiency syndrome. It is yet unknown what is the impact of HIV to the onset and progression of bone disease in BC. The purpose of the study was to determine the association of HIV infection and skeletal metastases in BC using skeletal scintigraphy. A retrospective analysis of 25 female BC patients' bone scans was performed. The 25 bone scans of 12 patients known HIV positive and 13 patients who were known HIV negative, of similar age and histology, were compared. All 13 HIV negative patients had a positive bone scan. Of the 12 HIV-positive patients, 4 patients on highly active antiretroviral therapy (HAART) had positive bone scans for skeletal metastases. The remaining eight HIV-positive patients had negative bone scans, of which six were on HAART and two were not on HAART. In our study, HIV infection was not found to be a contributing risk factor for skeletal metastases. From our small series, it appears that HIV patients and on HAART have a delay in the onset of skeletal metastases in BC.